2015
DOI: 10.1186/s13321-015-0052-z
|View full text |Cite
|
Sign up to set email alerts
|

When drug discovery meets web search: Learning to Rank for ligand-based virtual screening

Abstract: BackgroundThe rapid increase in the emergence of novel chemical substances presents a substantial demands for more sophisticated computational methodologies for drug discovery. In this study, the idea of Learning to Rank in web search was presented in drug virtual screening, which has the following unique capabilities of 1). Applicable of identifying compounds on novel targets when there is not enough training data available for these targets, and 2). Integration of heterogeneous data when compound affinities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 37 publications
(38 reference statements)
0
34
0
4
Order By: Relevance
“…The ranking prediction model f of learning-to-rank is represented as f ( ) = f ( ( , )) , where ≡ ( , ) is an input feature vector and is a feature map. In this section, we explain the method proposed by Zhang et al that uses the tensor product as [7] as well as the proposed method PKRank, which is a learning-to-rank-based VS using a pairwise kernel. The former method is a special case of the latter, as described presently.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ranking prediction model f of learning-to-rank is represented as f ( ) = f ( ( , )) , where ≡ ( , ) is an input feature vector and is a feature map. In this section, we explain the method proposed by Zhang et al that uses the tensor product as [7] as well as the proposed method PKRank, which is a learning-to-rank-based VS using a pairwise kernel. The former method is a special case of the latter, as described presently.…”
Section: Methodsmentioning
confidence: 99%
“…Rathke et al [6] proposed StructRank, which directly solves the ranking problem and focuses on the Molecular Profiling Research Center for Drug Discovery (molprof), National Institute of Advanced Industrial Science and Technology (AIST), 2-4-7 Aomi, Koto-ku, Tokyo 135-0064, Japan most promising compounds in terms of activity. Zhang et al [7] compared several learning-to-rank prediction models, and concluded that RankSVM is the best. Furthermore, they noted that learning-to-rank can treat multiple heterogeneous experimental data measured for different targets or platforms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…La interpretación de los resultados permitió deducir que la mejor aproximación de similaridad entre vectores es con respecto a los vectores activos. los efectos de Maldición de dimensionalidad en el algoritmo propuesto son mínimos debido al empleo de ordenamiento por magnitud de complejidad de los distintos acomplamientos existentes entre Candidatos a medicamento y vectores activos; lo que evita también altos costos computacionales, [23]. Aúnque no es necesario un conjunto de datos entrenamiento como lo exigen los Métodos de aprendizaje supervisado, la precisión del algoritmo propuesto es dificíl de determinar, [9]; pues como Medida de relevancia la Complejidad LMC es un indicador del grado de predicibilidad u orden que sustentan la relación de similaridad entre dos vectores; no se considera un cálculo de error con respecto a un patrón.…”
Section: Conclusionesunclassified
“…This is the reason why machine learning (ML) methods have recently gained such great popularity in the field of drug design. They are used both to select potential drug candidates from large compounds databases, but also to generate the structures of new chemical compounds de novo-or to optimize their physicochemical and pharmacokinetic properties [14][15][16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%